Remineralization of eroded enamel by a NaF rinse containing a novel calcium phosphate agent in an in situ model: a pilot study - Bennett T Amaechi; Ramalingam Karthikeyan; Poornima K Mensinkai; et al (Dove Medical Press, 2010)
Bennett T Amaechi1, Ramalingam Karthikeyan1, Poornima K Mensinkai1, Kaveh Najibfard1, Allen C Mackey2, Robert L Karlinsey21University of Texas Health Science Center at San Antonio, San Antonio, Texas, USA; 2Indiana Nanotech, Indianapolis, IN, USAPurpose: An in situ study evaluated the remineralization potential of 225 ppm fluoride (F) rinses with and without a calcium phosphate agent (TCP-Si-Ur) on eroded enamel.Methods: 20 human patients participated in this IRB approved study. Enamel blocks extracted from 20 human molars were assigned to each of the three study phases (G1, G2, G3). Each block was eroded using 1% citric acid (pH = 2.5), with a slice cut from each block to establish baseline lesion parameters (ie, integrated mineral loss ∆Z, and lesion depth LD) using transverse microradiography (TMR). Participants and assigned blocks were randomly divided into three 28-day phases. The blocks were mounted into modified orthodontic brackets and bonded to the buccal surface of one of the subject’s mandibular molars. The appliance remained in the subject’s mouth for 28 days. Prior to each study phase, participants observed a one-week-washout period using a fluoride-free dentifrice. In each phase, participants brushed with the fluoride-free dentifrice for 1 min, followed by one of the following coded treatments: G1: 225 ppm F + 40 ppm TCP-Si-Ur rinse (1 min); G2: 225 ppm F rinse (1 min); G3: no rinse (saliva-only). After each phase, appliances were removed and specimens were analyzed using TMR.Results: TMR data (ie, ∆Z and LD) revealed all three groups significantly remineralized eroded enamel (paired t-tests, P , 0.001). Net mineralization (% change in ∆Z, LD) were as follows (mean (std.dev.): G1: 44.1 (22.6), 30.5 (27.0); G2: 30.0 (7.4), 29.4 (10.5); G3: 23.8 (16.4), 25.7 (15.5). Furthermore, G1 was found to cause significantly more remineralization than G2 (P = 0.039) and G3, (P = 0.002).Conclusion: Mouthrinse containing 225 ppm F plus TCP-Si-Ur provided significantly greater remineralization relative to 225 ppm F only or saliva alone.Keywords: TCP-Si-Ur, fluoride, antierosion, tricalcium phosphate, double-blind